Phosphate organomineral fertilizer based on banana peels and coffee ground waste - Teixeira, Gustavo Fernandes; Santos, Kássia Graciele dos (Revista Brasileira de Ciência, Tecnologia e Inovação, 2023)
Population growth impacts all areas of society. Food production is one of the most pressing challenges resulting from population growth creating the need for optimized production and the application of innovative ideas in the agricultural sector to meet growing demands. A common method used to increase crop yields is the application of fertilizers. Aiming to reduce the impact of fertilizer application, specifically soil leaching, this study proposes the production of a slow-release organomineral fertilizer made from triple superphosphate. The proposed fertilizer was created via hand extrusion ensuring heterogeneity in the resulting fertilizer pellets. The sample F15 (9,2% of banana peel; 1,6% of starch; 57,3% of TSP and 32% of coffee waste) showed the slow-release time (1h for the release of 50% of the nutrients and 8h for the total release). Tests were then conducted seeking to analyze and improve their pyrolysis performance, biochar creation potential, and polymer coating in the soil. Test results enabled improvements to the fertilizer pellets via polymeric coating and thermal treatment. Both methods displayed good results, however, the thermal treatment method resulted in fertilizer loss due to unwanted reactions. Test results were analyzed using Weibull's kinetic model, which after great consideration, was deemed the most appropriate to analyze the properties of the proposed fertilizer. The development of pelleted and heat-treated organomineral fertilizers is promising because, in addition to saving the mineral fraction, it also provides an environmental benefit by reusing waste that would otherwise be thrown.